Implementasi Inovasi Pelayanan Perizinan - Heny Handayani (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This study aims to look at the implementation of licensing services innovation as an agent of investment growth in the new normal era in Sumedang Regency. The research method used is descriptive qualitative, with 8 informants consisting of 1 Head of Licensing Service, 1 Licensing Service Provider, 1 Data Information Analyst, and 5 Community Members. The data collection technique is literature study and field study consisting of observation, interviews, and documentation. The data analysis technique used is data reduction, data display, and verification which are interpreted qualitatively from the results of observations and interviews. Based on the results of the study, it was concluded that the implementation of licensing services, in general, had been running but not optimal, considering that the licensing service program was based online, it could be seen from the 9 indicators studied. The obstacles found were differences in the understanding of the applicant and the verifier, the flow of the licensing process was not yet simple, there were Decree Letter templates and requirements that were no longer relevant to the rules, and the licensing process was still not transparent (only monitoring), and there was no monitoring and evaluation facility related to the decree. which is issued. Efforts made to overcome these obstacles are the simplification of the process flow, the existence of direct communication facilities, refinement of Decree Letter templates and requirements that are adjusted to the latest regulatory developments, displaying the tracking application process transparently, as well as adding monitoring and evaluation facilities as well as notifications.